Lipoprotein(a): Levels and Reference Intervals Among People in Saudi Arabia - Jawi M; Al Mahdi HB; Daghistani H; Almoghrabi Y; Algahtani R; Tawati D; Algethami MR; Noorelahi Y; Awan Z (Diabetes, Metabolic Syndrome and Obesity, 2024)
Motasim Jawi,1 Hadiah Bassam Al Mahdi,2,3 Hussam Daghistani,4,5 Yousef Almoghrabi,4,5 Rami Algahtani,6 Dalal Tawati,7 Mohammed R Algethami,8 Yasser Noorelahi,9 Zuhier Awan4 1Department of Physiology, College of Medicine, University of Jeddah, Jeddah, Saudi Arabia; 2Al Borg Medical Laboratories, Al Borg Diagnostics, Research and Development Unit, Jeddah, Saudi Arabia; 3Department of Biological Sciences, Faculty of Science, King Abdulaziz University, Jeddah, Saudi Arabia; 4Department of Clinical Biochemistry, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 5Regenerative Medicine Unit, King Fahd Medical Research Center, King Abdulaziz University, Jeddah, Saudi Arabia; 6Department of Medicine, College of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 7Department of Obstetrics and Gynecology, King Abdullah Medical Complex, Jeddah, Saudi Arabia; 8Department of Family and Community Medicine, College of Medicine, University of Jeddah, Jeddah, Saudi Arabia; 9Department of Radiology, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Motasim Jawi, Department of Physiology, College of Medicine, University of Jeddah, Jeddah, Saudi Arabia, Tel +966 569191939, Email mmjawi@uj.edu.saPurpose: Blood Lp(a) concentration is recognized as an independent risk factor for cardiovascular disease (CVD). Population-based lipoprotein(a) (Lp[a]) research in Saudi Arabia is rare. Thus, the primary goal of this pilot study was to identify age- and sex-specific reference ranges for Lp(a) levels, in addition to the associations between Lp(a) levels and other atherosclerotic markers in Saudi individuals.Patients and methods: A five-year retrospective study of Lp(a) and lipid markers in Saudi patients was conducted using the Al-Borg diagnostics database (2015– 2020). The population sample consisted of 361 Saudi individuals aged 18– 93 years (162 males, 199 females). An immunoturbidimetric technique was used to determine Lp(a) concentration.Results: The mean and median Lp(a) levels in the study population were 35 nmol/L and 50 nmol/L, respectively. Sex and age did not influence Lp(a) values. Lp(a) values showed a minor correlation with other atherosclerotic markers when the Pearson correlation coefficient was used. In Saudi Arabia, the distribution of Lp(a) concentrations is skewed to the left, favoring lower values.Conclusion: Lp(a) levels in individuals residing in Saudi Arabia were comparable to those observed in other ethnic groups. Additionally, standardizing Lp(a) measurements according to sex and age may enhance broader applicability and facilitate comparisons across different populations. However, larger studies are required to provide more comprehensive data for comparison.Keywords: lipoprotein(a), lipids, cardiovascular disease, reference range, reference interval, Saudi Arabia